Adhesive composition, film and laminate

The adhesive composition with a polyester resin and isocyanate compounds addresses the high dielectric challenges of FPCs, achieving low dielectric properties and enhanced adhesion, suitable for FPCs and laminates.

JP2025006934APending Publication Date: 2025-01-17SEIKO PMC CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023107986
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing adhesive compositions for flexible printed circuit boards (FPCs) face challenges with high dielectric constants and loss tangents, poor solubility, and handling issues, failing to meet the requirements for low dielectric properties and adhesion to copper foil and polyimide films.

Method used

An adhesive composition containing a polyester resin with specific structural units derived from polystyrene and hydrogenated polybutadiene, combined with compounds having two or more isocyanate groups, and an organic solvent, which are formulated to achieve low dielectric constants and loss tangents, enhancing adhesion and flexibility.

Benefits of technology

The adhesive composition results in films with low dielectric constants and loss tangents, providing excellent adhesion to copper foil and polyimide films, suitable for manufacturing FPCs and other laminates, with improved handling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006934000001
    Figure 2025006934000001
  • Figure 2025006934000002
    Figure 2025006934000002
  • Figure 2025006934000003
    Figure 2025006934000003
Patent Text Reader

Abstract

To provide an adhesive composition that delivers higher solubility, lower dielectric constant, and lower dielectric loss tangent relative to the traditional technologies, exhibits superior adhesion to copper foil and polyimide films, and demonstrates superior solvent solubility and handleability, as well as a film and a laminate with superior flexibility, obtained by curing the adhesive composition.SOLUTION: An adhesive composition contains the following (1) and (2): (1) a polyester resin having structural units derived from polystyrene with carboxylic acid methyl ester groups at both ends and structural units derived from hydrogenated polybutadiene with hydroxyl groups at both ends; and (2) a compound having two or more isocyanate groups in each molecule, excluding compounds having double bonds within the same molecule.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition having low dielectric properties, good adhesion to substrates, and excellent solvent solubility and handling properties, a film having excellent flexibility, and a laminate including the film. More specifically, the present invention relates to an adhesive composition suitable for bonding electronic components, etc., particularly for the production of products related to flexible printed circuit boards (hereinafter also referred to as "FPCs"). [Background technology]

[0002] As electronic devices become smaller and lighter, the adhesive applications for electronic components are becoming more diverse, and the demand for adhesives to create metal and plastic laminates is increasing. FPC-related products that use adhesives include, for example, flexible copper-clad laminates (hereinafter also referred to as "FCCL") made by bonding copper foil to polyimide film, polyethylene naphthalate film, liquid crystal polymer (hereinafter also referred to as "LCP") film, etc., FPCs with electronic circuits formed on FCCL, FPCs with reinforced plates made by bonding FPCs and reinforced plates, and multilayer boards made by stacking and bonding FCCLs and FPCs.

[0003] Adhesives for making FCCLs and FPCs are required to have various properties such as low dielectric constant, low dielectric tangent, and other dielectric properties, as well as flexibility, in addition to adhesive properties. In particular, for FPCs that involve high-speed signal transmission, dielectric properties are important for reducing the transmission loss of electrical signals in the high-frequency range. Traditionally, styrene-based elastomers have been widely used as adhesive materials with the desired dielectric properties, but because conventional styrene-based elastomers have low solubility and problems with handling, there has been a demand for adhesives that can be dissolved at higher concentrations and with lower viscosity and have good handling properties.

[0004] For example, Patent Document 1 proposes an adhesive composition that has a sufficiently low relative dielectric constant and dielectric tangent, and a high elongation rate even with a high elastic modulus, and an adhesive sheet using the same, which is an adhesive composition that contains a modified polyphenylene ether resin, a styrene-based elastomer, and a silane coupling agent. However, there is room for improvement, for example, in that the concentration of the adhesive component needs to be reduced to 20% in consideration of handling properties, and because polyphenylene ether resin has a high melting point (softening point) and is hard at room temperature, when the blending ratio is set to fully satisfy the desired dielectric properties, the elastic modulus tends to increase and the elongation rate and flex resistance tend to decrease.

[0005] Patent Document 2 also proposes a resin composition that has a sufficiently low relative dielectric constant and dielectric tangent and is capable of suppressing resin flow, and an adhesive sheet and a bonding sheet for layer attachment using the same, which is an adhesive composition that contains a modified polyphenylene ether resin, a styrene-based elastomer, and an epoxy resin. However, in order to dissolve the resin in an amount of solvent of 90 mass% or less based on the solid content, a dissolving device such as a pressure kneader is required, and the fluidity of the solvent varnish is low, leaving room for improvement.

[0006] On the other hand, polyester has excellent heat resistance, chemical resistance, durability, and mechanical strength, and is therefore used in a wide range of applications, including films, PET bottles, fibers, toner, electrical components, adhesives, and pressure sensitive adhesives. In addition, polyester has high polarity due to its polymer structure, and is known to exhibit excellent adhesion to polar polymers such as polyester, polyvinyl chloride, polyimide, and epoxy resin, as well as metal materials such as copper and aluminum. Taking advantage of this property, its use as an adhesive for producing FCCLs and FPCs is being considered.

[0007] For example, Patent Document 3 discloses an adhesive composition containing a polyester resin having a specific glass transition temperature and dielectric loss tangent, which contains a structural unit derived from polyvalent carboxylic acids and a structural unit derived from polyhydric alcohols, as a polyester resin having a lower dielectric constant and a lower dielectric loss tangent than conventional polyester resins, and which is excellent in initial adhesion after curing and long-term durability in a humid and hot environment. Patent Document 4 also discloses an adhesive containing a polyester that exhibits desired dielectric properties by lowering the ester group concentration and decreasing the polarity of the polymer, as a polyester, film, and adhesive composition having excellent solvent solubility, heat resistance, and adhesion, and having low relative dielectric constant and dielectric loss tangent. However, in both of the disclosed techniques, although the dielectric properties before curing are evaluated, the dielectric properties of the film after curing, which are a problem during mounting, are not taken into consideration. In fact, there is no adhesive using a polyester resin that satisfies the recent required level of dielectric properties (relative dielectric constant after curing: 3.0 or less and dielectric loss tangent after curing: 0.0035 or less). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent Publication No. 2022-026390 [Patent Document 2] WO2022-255078 publication [Patent Document 3] JP 2022-051543 A [Patent Document 4] JP 2022-068240 A Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide an adhesive composition, a film, and a laminate using a polyester-based resin which has high solubility, a low dielectric constant, and a low dielectric tangent compared to conventional techniques, and which also has excellent adhesion to copper foil and polyimide film. [Means for solving the problem]

[0010] However, in view of these circumstances, the present inventors conducted extensive research and found that the above-mentioned problems could be solved by an adhesive composition containing a polyester resin containing a specific structural unit and a compound having two or more isocyanate groups in one molecule, and thus completed the present invention.

[0011] That is, the present invention provides: <1> An adhesive composition comprising the following (1) and (2): (1) A polyester resin having a structural unit derived from polystyrene with carboxylate methyl ester groups at both ends and a structural unit derived from hydrogenated polybutadiene with hydroxyl groups at both ends. (2) Compounds that have two or more isocyanate groups in one molecule, excluding compounds that have a double bond in the same molecule. <2> An adhesive composition comprising all of the following (1) to (3): (1) A polyester resin having a structural unit derived from polystyrene with carboxylate methyl ester groups at both ends and a structural unit derived from hydrogenated polybutadiene with hydroxyl groups at both ends. (2) Compounds that have two or more isocyanate groups in one molecule, excluding compounds that have a double bond in the same molecule. (3) Organic Solvent <3> An adhesive composition comprising all of the following (1) to (4): (1) A polyester resin having a structural unit derived from polystyrene with carboxylate methyl ester groups at both ends and a structural unit derived from hydrogenated polybutadiene with hydroxyl groups at both ends. (2) Compounds that have two or more isocyanate groups in one molecule, excluding compounds that have a double bond in the same molecule. (3) Organic Solvent (4) Polyphenylene ether resin having hydroxyl groups at both ends <4> The polyester resin is characterized in that the mass ratio of the structural unit derived from polystyrene having carboxylate methyl ester groups at both ends to the structural unit derived from hydrogenated polybutadiene having hydroxyl groups at both ends is 10 to 60: 90 to 40. <1> ~ <3> The adhesive composition according to any one of claims 1 to 5, <5> The above <1> ~ <3> A film obtained by curing the adhesive composition according to any one of claims 1 to 5. <6> The above <1> ~ <3> A laminate comprising a film obtained by curing the adhesive composition according to any one of claims 1 to 4. It is. Effect of the Invention

[0012] The polyester resin contained in the adhesive composition of the present invention has a low dielectric constant and a low dielectric tangent, particularly a low dielectric tangent, and forms a film that has excellent adhesion and flexibility after curing. In particular, such an adhesive composition is effective as an adhesive for producing a laminate consisting of a metal foil and a plastic film, for example, for bonding electronic materials, and particularly as an adhesive used in the production of FPCs such as FCCL, coverlays, and bonding sheets. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Polyester resin> The adhesive composition of the present invention contains at least a polyester resin having structural units derived from polystyrene having carboxylate methyl ester groups at both ends and structural units derived from hydrogenated polybutadiene having hydroxyl groups at both ends.

[0014] [Polystyrene with carboxylate methyl ester groups at both ends] The polystyrene having methyl carboxylate groups at both ends can be obtained by radical polymerization of a styrene monomer and / or a monomer containing a styrene derivative in an organic solvent using an initiator capable of introducing a methyl carboxylate group. An example of an initiator capable of introducing a methyl carboxylate group is dimethyl 2,2'-azobis(2-methylpropionate). When the dimethyl 2,2'-azobis(2-methylpropionate) is used as the initiator, dimethyl tetramethylsuccinate is generated from a part of it. Since dimethyl tetramethylsuccinate has a methyl ester, it is involved in an ester exchange reaction and inhibits polyester resin polymerization. Therefore, it is preferable to remove as much dimethyl tetramethylsuccinate as possible, which is contained as an impurity in the polystyrene having methyl carboxylate groups at both ends. The content of dimethyl tetramethylsuccinate contained as an impurity in the polystyrene having methyl carboxylate groups at both ends is preferably 2,000 ppm or less, more preferably 1,000 ppm or less, and particularly preferably 500 ppm or less.

[0015] In the present invention, the styrene derivative refers to a styrene derivative having only one vinyl group and having no reactive groups other than the vinyl group. Examples of the styrene derivative include α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene. The proportion of the styrene monomer and / or styrene derivative is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 100% by mass, of the raw material monomer component of the polystyrene having methyl carboxylate groups at both ends. In addition, from the viewpoint of versatility and handling, styrene monomer is preferred.

[0016] As long as the effect of the present invention is not hindered, other monomers having only one vinyl group or allyl group other than styrene monomers and the styrene derivatives can be used as the raw material monomers of the polystyrene having methyl carboxylate groups at both ends. In particular, when using a monomer having a reactive group or ester bond other than the vinyl group or allyl group, such as a carboxyl group, a hydroxyl group, or an amino group, as the other monomer, it is necessary to pay attention to the fact that the reactive group or ester bond causes a branched structure in the polyester resin. The proportion of the monomer having a reactive group or ester bond is usually preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 1% by mass or less of the raw material monomer components of the polystyrene having methyl carboxylate groups at both ends. Examples of other monomers include acrylic polymerizable monomers such as methyl acrylate, ethyl acrylate, and n-propyl acrylate.

[0017] The weight average molecular weight (hereinafter sometimes abbreviated as Mw) of the polystyrene having methyl carboxylate groups at both ends is preferably 1,000 or more and 20,000 or less. Since the π electrons of the phenyl group constituting the polystyrene contribute to the adhesion with the copper foil, if the Mw is 1,000 or more, the ratio of the structural unit derived from the polystyrene having methyl carboxylate groups at both ends in the polyester resin increases, and the adhesion is improved. In addition, if the Mw is 20,000 or less, the properties of the polystyrene part are not too strong, and the flexibility due to the structural unit derived from the hydrogenated polybutadiene having hydroxyl groups at both ends is not impaired, and the adhesion can be maintained. The Mw of the polystyrene having methyl carboxylate groups at both ends is more preferably 1,500 or more and 10,000 or less. In the present invention, the weight average molecular weight (Mw) and the number average molecular weight (hereinafter sometimes abbreviated as Mn) refer to the values ​​measured by gel permeation chromatography (GPC) of the soluble matter in tetrahydrofuran (hereinafter sometimes abbreviated as THF). The molecular weight measurement conditions are as follows. Equipment: Tosoh Corporation HLC-8320 Column: TSKGEL SUPERMULTIPORE HZ-H +TSKGEL SUPERMULTIPORE HZ-M Measurement temperature: 40℃ Sample concentration: 1.0g / L THF solution Solvent: THF Solution injection volume: 100μL Detector: Refractive index detector Molecular weight calibration curve: Created using standard polystyrene

[0018] [Hydrogenated polybutadiene with hydroxyl groups at both ends] The hydrogenated polybutadiene having hydroxyl groups at both ends is a hydrogenated product of polybutadiene having hydroxyl groups at both ends, and the polybutadiene having hydroxyl groups at both ends is a compound having a polymer chain derived from butadiene and hydroxyl groups at both ends of the polymer chain. The polymer chain derived from butadiene can act as an elastomer, and by having such a polymer chain, it is possible to impart adhesion and flexibility to the polyester resin. The hydrogenated polybutadiene having hydroxyl groups at both ends preferably has an average of 1.8 to 2.5 hydroxyl groups in the molecule. By having 1.8 or more hydroxyl groups in the molecule, the polymerization of the polyester resin can be increased in molecular weight without stopping, and by having 2.5 or less, gelation of the polyester resin due to crosslinking is suppressed, and the molecular weight can be increased, making it easier to obtain the excellent effects of the present invention.

[0019] Commercially available hydrogenated polybutadiene having hydroxyl groups at both ends can be used as is. Examples of commercially available hydrogenated polybutadiene having hydroxyl groups at both ends include NISSO-PB (registered trademark) GI-1000, GI-2000, and GI-3000 (all trade names, manufactured by Nippon Soda Co., Ltd.), KRASOL (registered trademark) HLBH-P2000, and HLBH-P3000 (all trade names, manufactured by Cray Valley Co., Ltd.). These may be used alone or in combination of two or more types depending on the amount of hydroxyl groups in the molecule.

[0020] From the viewpoint of the balance between viscosity and adhesive strength, the Mn of the hydrogenated polybutadiene having hydroxyl groups at both ends is preferably from 500 to 100,000, more preferably from 700 to 50,000, and most preferably from 900 to 10,000.

[0021] The hydrogenated polybutadiene having hydroxyl groups at both ends is most preferably GI-3000 (Mw 5,380) in consideration of the number average molecular weight, weight average molecular weight and amount of hydroxyl groups in the molecule of the hydrogenated polybutadiene.

[0022] [Ratio of polystyrene with carboxylate methyl ester groups at both ends and hydrogenated polybutadiene with hydroxyl groups at both ends] The ratio of polystyrene having carboxylate methyl ester groups at both ends and hydrogenated polybutadiene having hydroxyl groups at both ends constituting the polyester resin is preferably 10-60:90-40 by mass ratio (polystyrene having carboxylate methyl ester groups at both ends: hydrogenated polybutadiene having hydroxyl groups at both ends) in consideration of the amount of polyester resin having hydroxyl groups at both ends produced and the weight average molecular weight, which will be described later. By setting it within the above range, the polyester resin is excellent in balance between the improvement of film strength and adhesion due to the structural unit derived from polystyrene having carboxylate methyl ester groups at both ends and the flexibility due to the structural unit derived from hydrogenated polybutadiene having hydroxyl groups at both ends. The preferable mass ratio is 15-55:85-45 by mass ratio (polystyrene having carboxylate methyl ester groups at both ends: hydrogenated polybutadiene having hydroxyl groups at both ends), more preferably 20-50:80-50.

[0023] [Polyester resin with hydroxyl groups at both ends] The polyester resin used in the adhesive composition of the present invention is cured by a crosslinking reaction via terminal hydroxyl groups to form a film. Specifically, a polyester resin having hydroxyl groups at both ends is cured using a compound having two or more isocyanate groups in one molecule, which will be described later. Therefore, in order to obtain a film that satisfies the desired effect, it is preferable that the polyester resin used in the present invention contains a large amount of polyester resin having hydroxyl groups at both ends in addition to the design that takes into consideration both the adhesion and balance described above. The polyester resin having hydroxyl groups at both ends is sufficiently produced even with the above ratio, but it can usually be increased by increasing the number of moles of hydrogenated polybutadiene having hydroxyl groups at both ends relative to the number of moles of polystyrene having carboxylate methyl ester groups at both ends.

[0024] [Polyol other than hydrogenated polybutadiene with hydroxyl groups at both ends] In preparing the polyester resin, a polyol capable of reacting with the polystyrene having carboxylate methyl ester groups at both ends (hereinafter also referred to as "other polyol") may be used in combination with the hydrogenated polybutadiene having hydroxyl groups at both ends.

[0025] From the viewpoint of flexibility, the ratio of hydrogenated polybutadiene having hydroxyl groups at both ends is preferably 70% by mass or more, more preferably 80% by mass or more, based on the total amount of polyols (total of hydrogenated polybutadiene having hydroxyl groups at both ends and other polyols). The polyol may be composed only of hydrogenated polybutadiene having hydroxyl groups at both ends. The content of other polyols is preferably 0 to 30% by mass, or more preferably 0 to 10% by mass, based on the total amount of polyols.

[0026] Examples of the other polyols include dimer diols, bisphenol skeleton-containing monomers, aliphatic polyhydric alcohols, alicyclic polyhydric alcohols, aromatic polyhydric alcohols, polyester resin polyols, polyether polyols, polyacrylate polyols, polycarbonate polyols, polysiloxane polyols, polyisoprene polyols, polyolefin polyols, etc. The other polyols may be used alone or in combination of two or more.

[0027] In the present invention, the compound constituting the polyester resin preferably contains dimer diols as other polyols. Examples of dimer diols include dimer diols which are reduction products of dimer acids mainly having 36 to 44 carbon atoms derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc., and hydrogenated products thereof. Among them, hydrogenated products are preferred from the viewpoint of suppressing gelation during the production of the polyester resin.

[0028] When dimer diols are contained as other polyols, the content of the dimer diols relative to the total polyol is preferably 0.1 to 20% by mass. The content of the dimer diols relative to the total polyester resin is preferably 0.5 to 10% by weight. When dimer diols are contained, the adhesion tends to improve, and when the amount is too large, the dielectric loss tangent tends to deteriorate.

[0029] [Other raw materials that make up polyester resin] Polyester resin may contain polyvalent carboxylic acids. Examples of polyvalent carboxylic acids constituting polyester resin include dimer acids and condensed polycyclic aromatic compounds. Examples of dimer acids include dimer acids mainly having 36 to 44 carbon atoms derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc., and hydrogenated products thereof. Among them, hydrogenated products are preferred from the viewpoint of suppressing gelation during the production of polyester resin. As the condensed polycyclic aromatic compounds, examples of condensed polycyclic aromatic compounds of polyvalent carboxylic acids include naphthalenedicarboxylic acid, dimethyl naphthalenedicarboxylate, anthracene dicarboxylic acid, etc., among which naphthalenedicarboxylic acids are preferred from the viewpoint of price and availability, and dimethyl naphthalenedicarboxylate is more preferred from the viewpoint of reactivity. These can be used alone or in combination of two or more kinds.

[0030] [General raw material compounds that make up polyester resins] The polyester resin preferably has an ester group concentration of 500 eq / g or less. The low ester group concentration reduces the polarity of the polymer, thereby exhibiting low dielectric properties. The ester group concentration is preferably 400 eq / g or less, more preferably 300 eq / g or less.

[0031] [Calculation method for ester group concentration] The reciprocal of the weight-average molecular weight of the units formed from each acid component and each glycol component is 2×10 6 For example, in the case of a polyester resin consisting of polystyrene (Mw 3,680) with carboxylate methyl ester groups at both ends and GI-3000 (Mw 5,380), taking into account the methanol (molecular weight 32) that is eliminated, the weight-average molecular weight of the product unit is Mw = (3,680 + 5,380 - 32 × 2) = 8,996, so the ester group concentration is 222 eq / 10 6 g. Here, the product unit consisting of glycol (chemical formula 1 below) and polystyrene having methyl carboxylate groups at both ends (chemical formula 2 below) means chemical formula 3 below.

[0032] [ka]

[0033] [ka]

[0034] [ka]

[0035] [Production of polyester resin] Since polycondensation by ester exchange reaction between functional groups at the polymer terminals generally has low reactivity, it is preferable to use an organic solvent that can act as a compatibilizer for both polystyrene having carboxylate methyl ester groups at both ends and hydrogenated polybutadiene having hydroxyl groups at both ends in order to promote the reaction between them. Furthermore, a catalyst that promotes the ester exchange reaction can also be used in combination. Polycondensation can be carried out by distilling off the by-product methanol from the system while keeping the organic solvent that can act as a compatibilizer in the system. Thereafter, volatile components including the organic solvent are distilled off under reduced pressure to obtain a polyester resin having hydroxyl groups at both ends with a high molecular weight.

[0036] The organic solvent is preferably one or a mixture of two or more selected from aromatic organic solvents such as toluene, xylene, solvent naphtha, and Solvesso (registered trademark). From the viewpoint of the solubility of polystyrene having methyl carboxylate groups at both ends and hydrogenated polybutadiene having hydroxyl groups at both ends and the transesterification reaction temperature, xylene is particularly preferred. The amount of the organic solvent used may be an amount that can adjust the viscosity to promote the reaction. The amount of the organic solvent used is preferably 10 to 50 parts by mass relative to 100 parts by mass of the solute. By using an organic solvent in an amount of 10 parts by mass or more, the effect of compatibilization is sufficiently exhibited, and by using an organic solvent in an amount of 50 parts by mass or less, the transesterification reaction is promoted.

[0037] Examples of catalysts that can be used to promote the transesterification reaction include titanium compounds such as tetra-n-butyl titanate, tetraisopropyl titanate, and titanium oxyacetylcetonate, antimony compounds such as antimony trioxide and tributoxyantimony, germanium compounds such as germanium oxide and tetra-n-butoxygermanium, and acetates of magnesium, iron, zinc, manganese, cobalt, aluminum, etc. These catalysts can be used alone or in combination of two or more.

[0038] The temperature in a typical transesterification reaction between polystyrene having carboxylate methyl ester groups at both ends and hydrogenated polybutadiene having hydroxyl groups at both ends and other raw material compounds is 140 to 220°C, and the reaction time is 4 to 8 hours. The temperature in a typical polycondensation reaction is 160 to 240°C, and the reaction time is 4 to 20 hours.

[0039] [Polyester resin with terminal double bonds] In the present invention, the polyester resin may be used in combination with a polyester resin having terminal hydroxyl groups, into which a terminal double bond has been introduced by reacting a (meth)acrylate having an isocyanate group with some of the hydroxyl groups of the polyester resin.

[0040] [Crystallization of polyester resin] In the present invention, the polyester resin is preferably non-crystalline from the viewpoint of solubility in organic solvents and solution stability. A non-crystalline resin refers to a resin that has a glass transition temperature but does not have a melting point, and the presence or absence of crystallinity can be confirmed by the presence or absence of an endothermic peak due to crystal melting using a differential scanning calorimeter used for measuring the glass transition temperature described below.

[0041] [Glass transition temperature of polyester resin (hereinafter sometimes abbreviated as Tg)] The Tg of the polyester resin used in the present invention is preferably −50 to 0° C., more preferably −40 to −15° C., and particularly preferably −35 to −25° C. The polyester resin of the present invention does not lose flexibility even after curing because it contains polybutadiene having hydroxyl groups at both ends.

[0042] The method for measuring Tg is as follows: Tg is determined by measurement using a differential scanning calorimeter. Equipment: Discovery DSC25 manufactured by TA Instruments Japan Co., Ltd. Sample amount: 10 mg of resin Measurement method: In a nitrogen atmosphere, the sample was heated to 150°C (first heating), maintained at that temperature for 10 minutes, then cooled to -100°C at a rate of 10°C / min, maintained at that temperature for 10 minutes, and then heated at a rate of 10°C / min (second heating). Glass transition temperature: In the DSC curve obtained by the second heating, the intersection point (intersection 1) of a straight line extending the baseline on the low temperature side toward the high temperature side and a tangent line showing the maximum slope from the rising part of the peak to the peak apex, and the intersection point (intersection 2) of a straight line extending the baseline on the high temperature side toward the low temperature side and a tangent line showing the maximum slope from the rising part of the peak to the peak apex, are taken as the glass transition temperature. The temperature midway between the temperatures indicated by intersection 1 and intersection 2 is taken as the glass transition temperature.

[0043] [Dielectric properties of polyester resin] (Dielectric constant (hereinafter sometimes abbreviated as Dk)) The relative dielectric constant of the polyester resin used in the present invention at a frequency of 10 GHz under an environment of a temperature of 23° C. and a relative humidity of 50% RH is preferably 2.8 or less, more preferably 2.6 or less, particularly preferably 2.5 or less, and even more preferably 2.4 or less. By setting the relative dielectric constant within the above range, the transmission speed when used as a substrate can be maintained and transmission loss can be suppressed. (Dielectric tangent (hereinafter sometimes abbreviated as Df)) The polyester resin used in the present invention has a dielectric loss tangent of 0.0030 or less, preferably 0.0025 or less, and more preferably 0.0020 or less at a frequency of 10 GHz under an environment of a temperature of 23° C. and a relative humidity of 50% RH. By setting the dielectric loss tangent to the above range, the transmission loss when used in a substrate can be suppressed.

[0044] Polyester resins have terminal hydroxyl groups that increase the dielectric tangent, but because the concentration of ester groups is extremely low, the dielectric tangent before curing is also kept low.

[0045] The dielectric constant and dielectric loss tangent can be determined by the cavity resonator perturbation method using a network analyzer (Agilent Technologies E8361A) and a cylindrical cavity resonator (Kanto Electronics Application Development CP531). If the polyester resin is highly adhesive and it is difficult to prepare a measurement sample on its own, it is measured while inserted into a PTFE tube, and the dielectric properties of the polyester resin alone are calculated by subtracting the weight of the PTFE tube.

[0046] Thus, in the present invention, a polyester resin having a very small dielectric tangent can be obtained compared to conventional polyester resins. Since the polyester resin has a very small dielectric tangent, it is very useful as a raw material for adhesives used for bonding electronic materials and components, because it can suppress transmission loss in the high frequency range.

[0047] [Weight average molecular weight (Mw) of polyester resin] The Mw of the polyester resin used in the present invention is preferably 10,000 to 400,000, more preferably 20,000 to 300,000, and particularly preferably 50,000 to 250,000. When the Mw is higher than 10,000, the adhesion is good, and problems such as the polyester resin of the adhesive layer flowing and seeping out during press processing in producing flexible laminates such as FCCL and FPC can be prevented. Furthermore, when the Mw is lower than 400,000, the solution viscosity during coating can be kept within an appropriate range, and a uniform coating film can be obtained.

[0048] <Compounds with two or more isocyanate groups in one molecule> The adhesive composition of the present invention contains a compound having two or more isocyanate groups in one molecule, excluding compounds having a double bond in the same molecule. By containing a compound having two or more isocyanate groups in one molecule, crosslinking can occur via the terminal hydroxyl groups of the polyester resin, thereby curing the resin.

[0049] The reaction of curing the polyester resin with a compound having two or more isocyanate groups in one molecule can be carried out by applying the adhesive composition to a substrate and then raising the temperature to 40 to 200°C.

[0050] Examples of compounds having two or more isocyanate groups in one molecule include aliphatic diisocyanates such as tetramethylene diisocyanate and hexamethylene diisocyanate, aromatic diisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate and xylylene diisocyanate, alicyclic diisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, dimer acid diisocyanate and isophorone diisocyanate, and trimers of these isocyanate compounds. In the present invention, trimers of hexamethylene diisocyanate and isophorone diisocyanate are preferred from the viewpoints of reactivity, low dielectric properties, etc.

[0051] As a compound having two or more isocyanate groups in one molecule, commercially available products can be used, such as TORONATE (registered trademark, omitted below, manufactured by VENCOREX) IDT70B and HDT, and Desmodur (registered trademark, omitted below, manufactured by Sumika Covestro Urethane Co., Ltd.) N3300.

[0052] The added mass (NCOG) of the compound having two or more isocyanate groups in one molecule relative to the mass (OHG) of the polyester resin and the mass (SAG) of the hydroxyl-terminated polyphenylene ether resin, a co-crosslinking component described below, is preferably in the range of Formula 1 from the viewpoints of dielectric properties, crosslinkability, and stability over time, also known as the pot life of the adhesive composition, based on the hydroxyl equivalent (OHE) of the polyester resin, the hydroxyl-terminated polyphenylene ether resin (SAOHE), and the isocyanate equivalent (NCOE) of the compound having two or more isocyanate groups in one molecule.

[0053] (Formula 1) 0.8<(NCOG / NCOE)÷(OHG / OHE+SAG / SAOHE)<1.2

[0054] <Organic solvent> In addition, the adhesive composition of the present invention may further contain an organic solvent that the polyester resin is soluble in. By containing the organic solvent, the viscosity of the adhesive composition when applied to a substrate can be adjusted to an appropriate range, making it easy to handle when forming a coating film.

[0055] The organic solvent is preferably an aromatic organic solvent such as xylene used in producing a polyester resin, but may also be an alicyclic hydrocarbon organic solvent such as methylcyclohexane or ethylcyclohexane; a ketone organic solvent such as methyl ethyl ketone, methyl isobutyl ketone, or cyclohexanone; an alcohol organic solvent such as methyl alcohol, ethyl alcohol, isopropyl alcohol, or isobutyl alcohol; an ester organic solvent such as ethyl acetate or normal butyl acetate; an acetate organic solvent such as cellosolve acetate or methoxy acetate; or a mixture of two or more of these organic solvents. The amount of the organic solvent used is not particularly limited, and may be an amount that can be adjusted to an optimal viscosity when the adhesive composition of the present invention is applied. The amount of the organic solvent used is preferably 50 to 150 parts by mass relative to 100 parts by mass of the solute.

[0056] The adhesive composition of the present invention can be adjusted to a viscosity that is easy to handle by dissolving it in the amount of organic solvent used. In the present invention, a viscosity that is easy to handle is 10,000 mPa·s or less, more preferably 6,000 mPa·s or less, and 100 mPa·s or more, more preferably 500 mPa·s or more.

[0057] <Co-crosslinked component> The adhesive composition of the present invention may further contain a co-crosslinking component capable of co-crosslinking with a polyester resin having a terminal hydroxyl group or a terminal double bond. Although the co-crosslinking reduces adhesion to some extent compared to the case where the co-crosslinking is not performed, the durability (tensile strength) and heat resistance can be improved, so that an adhesive layer having a good balance of adhesion, durability and heat resistance can be obtained. Examples of the co-crosslinking component include 1,3,5-benzenetriol, 1,4-benzenediol, triallyl isocyanurate, monoalkyl diallyl isocyanurate, diallyl isocyanurate containing phosphorus-based substituents, modified polyphenylene ether resins having terminal hydroxyl groups or terminal double bonds, etc. Among them, modified polyphenylene ether resins having terminal hydroxyl groups are preferred.

[0058] In addition, from the viewpoint of reactivity with a polyester resin having a terminal double bond introduced therein and the dielectric properties of the adhesive, the modified polyphenylene ether resin may have at least one type of ethylenically unsaturated bond group at both ends thereof, such as a (meth)acryloyl group or a vinylbenzyl group.

[0059] A polyphenylene ether resin having hydroxyl groups at both ends, which is an example of a modified polyphenylene ether resin, can be obtained, for example, by oxidative coupling between a bifunctional phenolic compound and a monofunctional phenolic compound. A modified polyphenylene ether resin having vinylbenzyl groups at both ends, which is an example of a modified polyphenylene ether resin, can be obtained, for example, by converting the terminal phenolic hydroxyl groups of a polyphenylene ether resin into vinylbenzyl ether.

[0060] The Mw of the modified polyphenylene ether resin is preferably 1,000 to 4,000 from the viewpoints of compatibility with polyester-based resins and conformability to unevenness when the substrate and the wiring pattern side of a wiring-equipped resin substrate having a wiring pattern are thermally cured (pressed) via an adhesive layer.

[0061] Specific examples of modified polyphenylene ether resins that can be used include OPE-2St (modified polyphenylene ether resin having vinylbenzyl groups at both ends), OPE-2EA (modified polyphenylene ether resin having acryloyl groups at both ends, manufactured by Mitsubishi Gas Chemical Company, Inc.), NORYL (registered trademark) SA9000 (modified polyphenylene ether resin having methacryloyl groups at both ends, manufactured by SABIC), and NORYL (registered trademark) SA90 (modified polyphenylene ether resin having hydroxyl groups at both ends, manufactured by SABIC).

[0062] The content of the modified polyphenylene ether resin in the adhesive composition is 3 to 60 parts by mass, preferably 5 to 50 parts by mass, based on 100 parts by mass of the total of the polyester resin and the modified polyphenylene ether resin of the present invention. By making the content of the modified polyphenylene ether resin 60 parts by mass or less, it is possible to improve the bending resistance. Furthermore, by making the content of the modified polyphenylene ether resin 3 parts by mass or more, it is possible to improve the heat resistance. The polyphenylene ether resin may be used alone or in combination of two or more kinds.

[0063] In addition to the components listed above, the adhesive composition of the present invention may contain a conjugated diene polymer, a styrene elastomer, a modified styrene elastomer, or the like depending on the desired effect or purpose.

[0064] [Conjugated diene polymer] The conjugated diene polymer may be a polymer obtained by polymerizing a conjugated diene hydrocarbon, or a copolymer obtained by copolymerizing a conjugated diene hydrocarbon with a monoolefin unsaturated compound, as the adhesive composition. Specific examples of the conjugated diene polymer include butadiene polymer, isoprene polymer, and chloroprene polymer.

[0065] [Styrene-based elastomers, modified styrene-based elastomers] The adhesive composition may also contain a styrene-based elastomer or a modified styrene-based elastomer. Specific examples of the styrene-based elastomer include styrene-butadiene block copolymer, styrene-ethylene propylene block copolymer, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, styrene-ethylenebutylene-styrene block copolymer, and styrene-ethylenepropylene-styrene block copolymer, and specific examples of the modified styrene-based elastomer include those obtained by modifying these block copolymers with an unsaturated carboxylic acid. These various styrene-based elastomers may contain only one type, or may contain two or more types. Among the copolymers, styrene-ethylenebutylene-styrene block copolymer and styrene-ethylenepropylene-styrene block copolymer are preferred from the viewpoints of adhesiveness and electrical properties.

[0066] [Other ingredients] The adhesive composition of the present invention may contain other components other than those listed above in order to further improve its functionality. Examples of other components include inorganic fillers, coupling agents such as silane coupling agents, ultraviolet inhibitors, antioxidants, plasticizers, fluxes, flame retardants, colorants, dispersants, emulsifiers, elasticity reducing agents, diluents, defoamers, ion trapping agents, leveling agents, and catalysts. The content of other components is preferably 70% by mass or less, more preferably 0.05 to 60% by mass, particularly preferably 0.1 to 50% by mass, and even more preferably 0.2 to 40% by mass, based on the total amount of the adhesive composition of the present invention.

[0067] <Film> The film can be obtained by curing the adhesive composition or the adhesive layer. Here, the adhesive layer refers to a layer made of a coating and drying product of the adhesive composition formed on a substrate film or metal foil, and refers to a state in which at least the organic solvent has almost completely evaporated and lost fluidity (generally called "B stage" in this technical field). In addition, curing refers to crosslinking via terminal hydroxyl groups in the adhesive or adhesive layer, or crosslinking by polymerizing terminal double bonds. In the present invention, a layer that is partially cured as necessary in the production process (a layer that is cured in a later process) is also called an adhesive layer. The film has the effects of low dielectric properties, excellent adhesion, and excellent flexibility.

[0068] <Film properties> [Glass transition temperature (Tg)] The Tg of the film is preferably −50 to 0° C., more preferably −40 to −10° C., and particularly preferably −30 to −20° C. The polyester resin used in the present invention does not lose flexibility even after curing because it contains polybutadiene having hydroxyl groups at both ends.

[0069] [Dielectric properties] The dielectric properties of a film depend on the magnitude of the dipole moment in the adhesive component that constitutes the film, and it is known that the presence of polar groups with large dipole moments such as hydroxyl groups enhances the dielectric properties. In the case of a crosslinking system of carboxyl groups and epoxy groups in a conventional adhesive composition (carboxyl group-containing polyester resin + epoxy crosslinking agent), the carboxyl group, which has a small adverse effect on the dielectric tangent, reacts with the epoxy group to generate hydroxyl groups before and after curing, so that the dielectric tangent generally increases with curing. On the other hand, in the adhesive composition of the present invention, since the terminal hydroxyl group of the polyester resin is a primary hydroxyl group, not only can it be easily cured by a compound having two or more isocyanate groups in one molecule, but the amount of hydroxyl groups remaining in the film can be reduced as much as possible. Therefore, it is effective in maintaining the low dielectric properties of the film. As a result, the film of the present invention has low dielectric properties and low dielectric tangent.

[0070] In particular, the film of the adhesive composition of the present invention has excellent electrical properties at high frequencies. Specifically, the film of the adhesive composition of the present invention, which is a preferred embodiment and can be crosslinked by a reaction between a polyester resin having hydroxyl groups at both ends and a compound having two or more isocyanate groups in one molecule, has a relative dielectric constant (ε) of 3 or less in the frequency range of 1 to 80 GHz. In a more preferred embodiment of the film of the adhesive composition of the present invention, the dielectric loss tangent (tan δ) in the frequency range of 1 to 80 GHz is 0.0035 or less, in a further preferred embodiment, it is 0.0030 or less, and in a particularly preferred embodiment, it is 0.0025 or less. When the relative dielectric constant (ε) and the dielectric loss tangent (tan δ) in the frequency range of 1 to 80 GHz of the film of the adhesive composition of the present invention are in the above ranges, the electrical signal loss in the high frequency range of 3 GHz or more can be reduced.

[0071] [Adhesion] The adhesive layer of the adhesive composition has sufficient adhesion to both the roughened and glossy surfaces of the copper foil that constitutes the wiring of the FPC. The film of the adhesive composition can be adhered to a copper foil surface with a small degree of roughness. Therefore, the film of the adhesive composition is less susceptible to the effects of roughness, and transmission loss (transmission loss due to the skin effect) can be reduced. In addition, the film of the adhesive composition has sufficient adhesion to polyimide films and LCP films used as substrate materials for FPCs.

[0072] The adhesion can be evaluated by measuring the 180° peel strength (N / cm) using the method described below, and the higher the peel strength value, the better the adhesion to the substrate. The peel strength can be evaluated by cutting a laminate with an adhesive layer with substrates bonded to both sides into a 1 cm wide test piece after curing under a pressure of 0.04 MPa (curing for 2 hours at 130°C, then curing for 1 hour at 170°C), fixing the test piece to a plastic plate using double-sided tape, and performing a 180° peel test (pulling speed 20 mm / min) using a Tensilon tester (A&D RTC-1150A) in an environment at a temperature of 25°C. Specifically, in a preferred embodiment of the adhesive composition, which can be crosslinked by reaction between a polyester resin having hydroxyl groups at both ends and a compound having two or more isocyanate groups in one molecule, the 180° peel strength from a roughened copper foil surface and the 180° peel strength from a roughened copper surface to a polyimide film are 4 N / cm or more, more preferably 6 N / cm or more, and particularly preferably 8 N / cm or more.

[0073] <Laminate with Adhesive Layer> The laminate having an adhesive layer comprises an adhesive layer made of an adhesive composition, and a substrate film in contact with at least one surface of the adhesive layer.

[0074] In a laminate having an adhesive layer, the thickness of the adhesive layer is preferably 5 to 100 μm, more preferably 10 to 70 μm, and even more preferably 10 to 50 μm. The thicknesses of the base film and the adhesive layer are selected depending on the application, but there is a tendency for the base film to be thinner in order to improve electrical properties.

[0075] Examples of laminates having an adhesive layer include a coverlay film and a bonding sheet. A coverlay film is a laminate in which it is difficult to peel the adhesive layer from the base film. On the other hand, a bonding sheet is a laminate in which an easily peelable release film is used as the base film, and the release film is peeled off when used for adhesion. The bonding sheet may have an adhesive layer between two release films. When the laminate having an adhesive layer is a coverlay film, a release film used for the bonding sheet may be laminated on the surface of the adhesive layer as necessary for storage or the like.

[0076] Examples of the substrate film used in the coverlay film include a polyimide film, a polyether ether ketone film, a polyphenylene sulfide film, an aramid film, a polyethylene naphthalate film, a liquid crystal polymer film, a polyethylene terephthalate film, a polyethylene film, a polypropylene film, a polymethylpentene film, and a fluorine-based resin film, etc. Among these, from the viewpoints of adhesiveness and electrical properties, a polyimide film, a polyethylene naphthalate film, and a liquid crystal polymer film are preferred, and a polyimide film and a liquid crystal polymer film are more preferred.

[0077] Such substrate films are commercially available, and examples of polyimide films include Kapton (registered trademark, manufactured by DuPont-Toray Co., Ltd.), Xenomax (registered trademark, manufactured by Toyobo Co., Ltd.), Upilex S (registered trademark, manufactured by Ube Industries, Ltd.), and Apical (registered trademark, manufactured by Kaneka Corporation). Examples of polyethylene naphthalate films include Teonex (registered trademark, manufactured by Teijin DuPont Films Co., Ltd.). Examples of liquid crystal polymer films include Vecstar (registered trademark, manufactured by Kuraray Co., Ltd.), Viac (registered trademark, manufactured by Ise Murata Manufacturing Co., Ltd.), and Pericule LCP (Chiyoda Integre Co., Ltd.). The substrate film can also be made by forming the corresponding resin into a film of a desired thickness.

[0078] Examples of the base film (release film) used in the bonding sheet include polyethylene terephthalate film, polyethylene film, polypropylene film, silicone release-treated paper, polyolefin resin-coated paper, polymethylpentene film, fluorine-based resin film, etc. There are no particular limitations as long as it is peelable, but release-treated polyethylene terephthalate film is preferred in terms of availability, cost, and processability during coating and lamination.

[0079] Such release films are also commercially available, and examples that can be used include Lumirror (registered trademark, manufactured by Toray Advanced Film Co., Ltd.), Toyobo Ester (registered trademark) Film (manufactured by Toyobo Co., Ltd.), Aflex (registered trademark, manufactured by AGC Inc.), and Opulent (registered trademark, manufactured by Mitsui Chemicals Tocello Co., Ltd.).

[0080] As a method for producing a laminate having an adhesive layer, for example, the above-mentioned adhesive composition can be applied to the surface of a base film and then dried to produce a laminate having an adhesive layer formed thereon.

[0081] <Flexible copper clad laminate> The flexible copper clad laminate has at least one laminated structure in which a base film and a copper foil are bonded together via an adhesive layer. The adhesive layer has excellent adhesion to the copper foil, so that the flexible copper clad laminate of the present invention has excellent shape stability.

[0082] A method for producing a flexible copper clad laminate includes, for example, a method in which a copper foil is placed in surface contact with the adhesive layer of a laminate having an adhesive layer, thermal lamination is performed at 80°C to 150°C, and the adhesive layer is further cured by a curing treatment. The curing treatment conditions can be, for example, 100°C to 200°C, 30 minutes to 6 hours, and 0.01 to 50 MPa. The copper foil is not particularly limited, and it is preferable to use an electrolytic copper foil, a rolled copper foil, or the like.

[0083] It is also possible to manufacture a flexible copper-clad laminate without using a laminate with an adhesive layer. For example, the adhesive composition is applied to the bonded surface of a copper foil and dried in the same manner as for a laminate with an adhesive layer. The remaining substrate film is then placed on the dried adhesive layer, and the adhesive layer is cured by the above-mentioned thermal lamination and curing treatment.

[0084] <Application> The adhesive composition of the present invention is excellent in low dielectric constant and low dielectric tangent, especially low dielectric tangent, and the film obtained using them is also excellent in low dielectric constant and low dielectric tangent, excellent in flexibility, low modulus of elasticity, and effective for adhesion of substrates made of various materials such as resins and metals, and is particularly suitable as an adhesive for producing a laminate of a metal foil and a plastic film, for example, an adhesive used for bonding electronic material members. Examples of the "electronic material member" in the present invention include flexible printed circuit boards, coverlays, bonding sheets, etc. Examples of those produced by bonding electronic material members include flexible laminates such as flexible copper-clad laminates and flexible printed circuit boards. The flexible laminate is, for example, a laminate in which "flexible flexible substrate / adhesive layer / conductive metal layer made of copper, aluminum, or an alloy thereof" are laminated in sequence, and the adhesive composition of the present invention can be used as the adhesive constituting the adhesive layer. In addition to the various layers described above, the flexible laminate may further include other insulating layers, other adhesive layers, and other conductive metal layers. EXAMPLES

[0085] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. Unless otherwise specified, all numerical values ​​indicated by "parts" and "%" below are based on mass.

[0086] <Synthesis example of polystyrene (PS) with carboxylate methyl ester groups at both ends> (PS-1) A reaction vessel equipped with a thermometer, a stirrer, a reflux tower, a dropping funnel, and a nitrogen inlet tube was charged with 50 parts by mass of toluene as an organic solvent, and 100 parts by mass of styrene monomer (St) and 24 parts of dimethyl 2,2'-azobis(2-methylpropionate) as an initiator were dropped into the vessel under toluene reflux over a period of 5.5 hours to carry out radical polymerization.

[0087] After the dropwise addition was completed, the mixture was kept under reflux for 30 minutes, and then the reflux tower was changed to a distillation system. After distillation up to 170°C, the initiator decomposition product dimethyl tetramethylsuccinate was distilled under reduced pressure until it was 1,000 ppm or less. The reaction product was then taken out to obtain polystyrene with methyl carboxylate groups at both ends (PS-1).

[0088] (PS-2) Polystyrene having carboxylate methyl ester groups at both ends (PS-2) was synthesized in the same manner as polystyrene having carboxylate methyl ester groups at both ends (PS-1), except that the amount of initiator used in the synthesis was changed as shown in Table 1.

[0089] [Table 1] <Synthesis of polyester resin (A-1)> In a reaction vessel equipped with a reflux tower equipped with a thermometer, a stirrer, a fractionator filled with toluene in advance, and a nitrogen inlet tube, 25 parts by mass of xylene as an organic solvent, polystyrene (PS-1) with methyl carboxylate groups at both ends, and NISSO-PB (registered trademark) GI-3000 (manufactured by Nippon Soda Co., Ltd.) as hydrogenated polybutadiene with hydroxyl groups at both ends were charged in the amounts shown in Table 2, and the inside of the reaction vessel was replaced with nitrogen, and the temperature was raised while stirring. When the temperature in the reaction vessel reached 140°C, tetraisopropyl titanate (trade name: Orgatix (registered trademark) TA-10, manufactured by Matsumoto Fine Chemical Co., Ltd.) was added as a catalyst, and the temperature in the reaction vessel was further increased from 160°C to 170°C, and the by-product (methanol) was distilled out of the system under xylene reflux, and the transesterification reaction was carried out for 10 hours.

[0090] The fractionator was then removed and replaced with a distillation system to remove the xylene. After the internal temperature reached 175°C, the pressure inside the reactor was reduced to further increase the molecular weight, and a polyester resin (A-1) was obtained after 20 hours of reduced pressure reaction.

[0091] <Synthesis of polyester resins (A-2) to (A-6)> Except for changing the types and amounts of raw materials as shown in Table 2, polyester resins (A-2) to (A-6) were synthesized in the same manner as for (A-1).

[0092] <Preparation of Organic Solvent Varnishes (B-1) to (B-6) of Polyester Resin> The obtained polyester resins (A-1) to (A-6) were dissolved in an organic solvent prepared with the same mass parts as the polyester resin, using methyl ethyl ketone (MEK) and methylcyclohexane (MCH) in the ratio shown in Table 2, to obtain organic solvent varnishes (B-1) to (B-6) (containing 50% polyester resin) of the polyester resins (A-1) to (A-6). As shown in Table 2, it was confirmed that the viscosities were easy to handle.

[0093] [Table 2] PS: Polystyrene with carboxylate methyl ester groups at both ends GI3000: Hydrogenated polybutadiene with hydroxyl groups at both ends (product name: GI-3000, manufactured by Nippon Soda Co., Ltd.) P2033: Dimer diol (product name: Pripol (registered trademark) 2033, manufactured by Croda) TA: Tetraisopropyl titanate (product name: TA-10, manufactured by Matsumoto Fine Chemical Co., Ltd.)

[0094] The physical properties of the polyester resins (A-1) to (A-6) are shown in Table 3. The physical properties of the polyester resins were evaluated as follows.

[0095] <Evaluation of physical properties of polyester resin> [Preparation of polyester resin film for evaluation of Dk, Df, and glass transition temperature] The polyester resin organic solvent varnishes (B-1) to (B-6) were applied to a release film so that the thickness after drying would be 25 μm, and the resin film obtained by drying (drying at 100°C for 20 minutes) was then covered with a release film.

[0096] [Measurement of Dk and Df] The release film was peeled off from the resin film, and the Dk and Df at 10 GHz were measured. The measurements were performed in an environment of 25°C and 50% RH using a cavity resonator perturbation method with a network analyzer (Agilent Technologies E8361A) and a cylindrical cavity resonator (Kanto Electronics Application Development CP531).

[0097] [Measurement of glass transition temperature (Tg)] The release film was peeled off from the prepared resin film, and the glass transition temperature was measured using a differential scanning calorimeter (DSC25 manufactured by TA Instruments) at a measurement temperature of −100 to 150° C. and a measurement speed of 10° C. / min.

[0098] [Acid value and hydroxyl value measurement] Measurements were performed in accordance with the provisions of JIS K0070.

[0099] [Table 3] Ester group concentration: 2×10 of the reciprocal of the weight average molecular weight of the units formed from polystyrene with carboxylate methyl ester groups at both ends, hydrogenated polybutadiene with hydroxyl groups at both ends, and dimer diol 6 Double

[0100] <Production Example of Adhesive Composition> Example 1 In a flask equipped with a thermometer, a stirrer, a reflux tower, and a nitrogen inlet tube, 200 parts by mass of the organic solvent varnish (B-1) of the polyester resin obtained above (100 parts by mass as polyester resin) was added and mixed uniformly to obtain an adhesive composition (C-1).

[0101] (Examples 2 to 12) Adhesive compositions (C-2) to (C-12) were obtained in the same manner as (C-1), except that the polyester resin organic solvent varnish, the compound having two or more isocyanate groups in one molecule, and the co-crosslinking component were changed as shown in Table 4. SA90 was mixed as a MEK varnish containing 50% SA90.

[0102] [Table 4] SA90: Modified polyphenylene ether resin having terminal hydroxyl groups (product name: NORYL (registered trademark) SA90, manufactured by SABIC) IDT: Isophorone diisocyanate trimer (product name: TORONATE IDT70B, manufactured by VENCOREX) N3300: Hexamethylene diisocyanate trimer (product name: Sumidur N3300, manufactured by Sumika Covestro Urethane Co., Ltd.)

[0103] <Film evaluation> [Preparation of film for evaluation of Dk, Df, and glass transition temperature] The adhesive compositions (C-1) to (C-12) were applied to a release film so that the thickness after curing would be 25 μm, and then the B-stage film obtained by pre-treatment (drying at 100°C for 20 minutes) was covered with a release film and cured (curing at 160°C for 1 hour, followed by curing at 175°C for 1 hour) to produce a film.

[0104] [Measurement of Dk and Df] The release film was peeled off from the prepared film, and the film was subjected to measurement of Dk and Df at 10 GHz. The Dk and Df measurements were performed in the same manner as for the resin film. Note that these are the required levels for dielectric properties in recent years (relative permittivity after curing: 3.0 or less and dielectric loss tangent after curing: 0.0035 or less).

[0105] [Measurement of glass transition temperature] The release film was peeled off from the prepared film, and the glass transition temperature was measured in the same manner as for the resin film.

[0106] [Preparation of polyimide film / copper foil adhesion evaluation laminate] The adhesive compositions (C-1) to (C-12) were applied to a release film so that the thickness after curing would be 25 μm, and then the coating was pretreated (dried at 100°C for 20 minutes). The coating was then transferred to the roughened surface of a low-roughness copper foil for high frequencies, covered with a polyimide (hereinafter sometimes abbreviated as PI) film, and cured under a pressure of 0.04 MPa (cured at 160°C for 1 hour, then cured at 175°C for 1 hour) to obtain a laminate. [Film thickness] 25μm [Copper foil] Electrolytic copper foil CF-T9DA-SV-18 (manufactured by Fukuda Metal Foil and Powder Co., Ltd., thickness 18 μm, roughness of roughened surface Rz 0.7 μm) [Polyimide film] Kapton (registered trademark) EN (manufactured by Toray DuPont Co., Ltd., thickness 25 μm)

[0107] [Adhesion] Each of the laminates obtained above for evaluating adhesion was cut into 1 cm width to prepare test pieces. The test pieces were fixed to a plastic plate using double-sided tape and evaluated in a 180° peel test (tensile speed 20 mm / min) using a Tensilon tester (A&D RTC-1150A) in an environment at a temperature of 25°C. Note that the required level of 180° peel strength for substrates in recent years is 4 N / cm or more.

[0108] <Evaluation Results> The evaluation results are summarized in Table 5.

[0109] [Table 5] From Tables 2, 3, and 4, it was shown that the adhesive compositions (Examples 1 to 12) satisfying the requirements of the present invention have excellent low dielectric constants and low dielectric tangents, particularly low dielectric tangents, and are excellent in the balance between the handleability of the adhesive composition and the adhesion of the film obtained by curing the adhesive composition, while using a polyester resin having a structural unit derived from polystyrene with carboxylate methyl ester groups at both ends and a structural unit derived from hydrogenated polybutadiene with hydroxyl groups at both ends as raw materials, and a compound having two or more isocyanate groups in one molecule, and using less organic solvent than the conventional technology. Furthermore, from Tables 4 and 5, it was shown that the films obtained by curing these adhesive compositions also have excellent low dielectric constants and low dielectric tangents, and are excellent in the balance between the handleability of the adhesive composition and the adhesion of the film obtained by curing the adhesive composition.

Claims

1. An adhesive composition comprising the following (1) and (2): (1) A polyester resin having a structural unit derived from polystyrene having carboxylate methyl ester groups at both ends and a structural unit derived from hydrogenated polybutadiene having hydroxyl groups at both ends. (2) Compounds having two or more isocyanate groups in one molecule, excluding compounds having a double bond in the same molecule.

2. An adhesive composition comprising all of the following (1) to (3): (1) A polyester resin having a structural unit derived from polystyrene having carboxylate methyl ester groups at both ends and a structural unit derived from hydrogenated polybutadiene having hydroxyl groups at both ends. (2) Compounds having two or more isocyanate groups in one molecule, excluding compounds having a double bond in the same molecule. (3) Organic Solvent

3. An adhesive composition comprising all of the following (1) to (4): (1) A polyester resin having a structural unit derived from polystyrene having carboxylate methyl ester groups at both ends and a structural unit derived from hydrogenated polybutadiene having hydroxyl groups at both ends. (2) Compounds having two or more isocyanate groups in one molecule, excluding compounds having a double bond in the same molecule. (3) Organic Solvent (4) Polyphenylene ether resin having hydroxyl groups at both ends

4. The adhesive composition according to any one of claims 1 to 3, characterized in that the mass ratio of the structural units derived from polystyrene having carboxylate methyl ester groups at both ends constituting the polyester resin:the structural units derived from hydrogenated polybutadiene having hydroxyl groups at both ends is = 10-60:90-40.

5. A film obtained by curing the adhesive composition according to any one of claims 1 to 3.

6. A laminate comprising a film obtained by curing the adhesive composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Resin composition and adhesive sheet using the same

    JP2022026390A

  • Polyester-based resin, adhesive composition and adhesive

    JP2022051543A

  • Polyester, film and adhesive composition, as well as adhesive sheet, laminate and printed wiring board

    JP2022068240A

  • Resin composition, production method therefor, adhesive film, and bonding sheet for interlaminar bonding

    WO2022255078A1